2018
DOI: 10.1556/1646.10.2018.43
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychosocial determinants in predicting adherence to treatment in patient with hypertension

Abstract: Introduction Non-adherence in patients with hypertension directly exacerbates clinical outcomes. The purpose of the present research is to study the recognition of the relationships between the perceived social support and self-efficacy and the satisfaction of health care agents and the interaction of the patient with therapeutic personnel and access to health care and the behaviors of adherence to treatment in the patients who suffer hypertension. Materials and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
0
10
0
1
Order By: Relevance
“… 15 , 16 On the other hand, other investigations indicated social support was not associated with treatment adherence. 17 , 18 Inappropriate advice from friends and family members may have unintentional negative influences on adherence and self-management behaviors. 19 Evidence remains inconsistent for relationships between social support and treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 On the other hand, other investigations indicated social support was not associated with treatment adherence. 17 , 18 Inappropriate advice from friends and family members may have unintentional negative influences on adherence and self-management behaviors. 19 Evidence remains inconsistent for relationships between social support and treatment adherence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, socio-demographic factors including gender, age, education level, occupational status, or even race; ( Abegaz et al, 2017 ; Lee et al, 2017 ; Fatani et al, 2019 ) socio-economic status including annual income and medical insurance; ( Boima et al, 2015 ; Nielsen et al, 2017 ) clinical characteristics for patients including family disease history, number of prescribed drugs, comorbidity, and duration of hypertension ( Choi et al, 2018 ; Uchmanowicz et al, 2019 ). Most importantly, psychosocial factors also exert significant influence on medication adherence, including depressed emotion, perceived severity of disease, self-rated health, perceived symptoms, and self-efficacy ( Al-Noumani et al, 2018 ; Asgari et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These include socio-demographic factors (Abegaz et al, 2017; Nurhussein et al, 2018; Fatani et al, 2019; Uchmanowicz et al, 2019), such as gender, age, education level, occupational status, or even race; socio-economic status, such as annual income and medical insurance (Boima et al, 2015; Nielsen et al, 2017); and family disease history, number of prescribed drugs, comorbidity, and duration of hypertension as clinical disease-related factors (Choi et al, 2018; Williams et al, 2018; Uchmanowicz et al, 2019). Furthermore, psychosocial factors also influence medication adherence, such as depressed emotion, perceived severity of disease, self-rated health, perceived symptoms, and self-efficacy (Al-Noumani et al, 2018; Asgari et al, 2019). Knowledge of hypertension and patients’ literacy (Boima et al, 2015; Shirindi et al, 2016; Pan et al, 2017) were also found to be predictors of medication adherence.…”
Section: Introductionmentioning
confidence: 99%